Enhancing Cushing’s disease diagnosis: exploring the impact of desmopressin on ACTH gradient during BIPSS - Almeida, Tobias Skrebsky de; Rodrigues, Ticiana da Costa; Costenaro, Fabíola; Scaffaro, Leandro Armani; Farenzena, Maurício; Gastaldo, Fernando; Czepielewski, Mauro Antônio (Frontiers in Endocrinology, 2023)
>1.4 before and >2.8 after stimulation, the sensitivity was 87.2% and 89.6%, respectively, with a combined sensitivity of 91.7%. Receiver operating characteristic (ROC) curve analysis determined optimal cutoff values of 1.2 before stimulation and 1.57 after stimulation, resulting in a sensitivity of 93.6% and 93.8%, respectively, with a combined sensitivity of 97.9%. Specificity remained at 100% throughout all analyses. Among the 43 patients who responded positively to stimulation, 42 (97.7%) did so within the first three minutes, and all 43 (100%) did so within the first five minutes. None of the assessed clinical variables predicted the ACTH response to stimulation in BIPSS with statistical significance. Discussion ACTH stimulation with desmopressin during BIPSS improves the accuracy of IPS:P, making it a valuable tool for investigating ACTH-dependent Cushing's syndrome. Considering the low risk of complications, we recommend the use of desmopressin stimulation during BIPSS for the differential diagnosis of ACTH-dependent CS.